PENGARUH PENDAPATAN ASLI DAERAH, PENDAPATAN TRANSFER, DAN LAIN-LAIN PENDAPATAN YANG SAH TERHADAP BELANJA MODAL PADA KABUPATEN/KOTA DI SUMATERA UTARA - Iqbal, Muhammad (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study intends to examine the impact of local income (PAD), transfer income and other lawful revenue on district/city capital expenditure in North Sumatra Province From 2021 to 2023 both partially and simultaneously. The research used a quantitative technique, with data collected from secondary sources, specifically the website of the Directorate General of Fiscal Balance.This research used a ninety nine samples, which was determined through purposive sampling. Multiplied linear regression analysis was applied to examine the data using SPSS. According to the analysis, just PAD and transfer income have an impact on capital expenditure, but other lawful revenue do not. Simultaneously, PAD, transfer income and other lawful revenue have a influence on capital expenditures.